Role of Flavonoids as Epigenetic Modulators in Cancer Prevention and Therapy - Fatima, Nishat; Baqri, Syed Shabihe Raza; Bhattacharya, Atrayee; Koney, Nii Koney-Kwaku; Husain, Kazim; Abbas, Ata; Ansari, Rais A. (Frontiers in Genetics, 2021)
Epigenetic regulation involves reversible changes in histones and DNA modifications that can be inherited without any changes in the DNA sequence. Dysregulation of normal epigenetic processes can lead to aberrant gene expression as observed in many diseases, notably cancer. Recent insights into the mechanisms of DNA methylation, histone modifications, and non-coding RNAs involved in altered gene expression profiles of tumor cells have caused a paradigm shift in the diagnostic and therapeutic approaches towards cancer. There has been a surge in search for compounds that could modulate the altered epigenetic landscape of tumor cells, and to exploit their therapeutic potential against cancers. Flavonoids are naturally occurring phenol compounds which are abundantly found among phytochemicals and have potentials to modulate epigenetic processes. Knowledge of the precise flavonoid-mediated epigenetic alterations is needed for the development of epigenetics drugs and combinatorial therapeutic approaches against cancers. This review is aimed to comprehensively explore the epigenetic modulations of flavonoids and their anti-tumor activities.